Translation and Validation of Developmental Coordination Disorder Questionnaire in Urdu Language for Developmental Coordination Disorder Population - Rida Khawar Dar, Shoaib Waqas, Muhammad Tariq, Hafiz Muhammad Asim, Asifa Javaid, Imran Ghafoor, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To translate developmental coordination disorder questionnaire in Urdu language and validate its psychometric properties for cross cultural adaptation. Methods: This validation study was done at the Lahore College of Physical Therapy. The Developmental Coordination Disorder Questionnaire (DCDQ) was translated into Urdu utilizing Bombardier, Beaton, and Guillemin's cross-cultural adaption principles. The forward and backward translations were completed by two separate translators, one of whom is a medical professional professor and the other an Urdu language professor. The final certified version of DCDQ-Urdu was confirmed by bilingual professionals. The validated version's reliability was then evaluated on 28 children with developmental coordination disorder. Results: After population testing, the Cranach's alpha of the DCDQ-Urdu version was 0.873. The inter item correlation of the DCDQ-Urdu for three domains, control during movement, fine motor/handwriting, and general coordination, with total DCDQ score is 0.386, 0.312, and 0.3002, respectively, and after population testing is 0.273, 0.303, and 0.397. The original English and translated DCDQ-Urdu versions had a significant association (Spearman's rho 0.951 p 0.000).Test retest reliability ranged from 0.504 to 0.721. Conclusion: The Urdu version of the Developmental Coordination Disorder Questionnaire has good internal consistency and fair inter-item correlation, making it suitable for use as a screening tool for parents of children with and without impaired motor coordination. Keywords: Developmental Coordination Disorder, DCDQ-Urdu version, Motor skill impairment